Answer :
Answer:
(f•g)(3) = -7
Step-by-step explanation:
f(x)=-2x + 7
g(x) = x^2 – 2
(f•g)(3) = -2(x² - 2) + 7
(f•g)(3) = -2x² + 4 +7
(f•g)(3) = -2x² + 11
(f•g)(3) = -2(3)² + 11
(f•g)(3) = -2(9) + 11
(f•g)(3) = -18 + 11
(f•g)(3) = -7
Answer:
= 7
Step-by-step explanation:
If f(x) = -2x + 7 and g(x) = x^2 – 2, what is (f•g)(3)?
(f. g) = (-2x + 7)(x² - 2)
= -2x (x² - 2) +7( x² -2)
=-2x³ + 4x + 7x² - 14
(f. g) (3) means when x = 3
= -2x³ +4x + 7x² - 14
= -2(3)³ + 4(3) + 7(3)² - 14
= -2(27) +12 +7(9) - 14
= -54 +12+63-14
=75 - 68
= 7
I hope this was helpful, please mark as brainliest